2016
DOI: 10.21666/mskuefd.59611
|View full text |Cite
|
Sign up to set email alerts
|

Müzik Öğretmeni Adaylarının Benimsedikleri Eğitim Felsefelerinin Çeşitli Değişkenler Açısından İncelenmesi

Abstract: This study aims to determine educational philosophy adopted by music teacher candidates and to examine in terms of different variables. The sample for the study consist of music teacher candidates who were enrolled in Muğla Sıtkı Koçman University Faculty of Education, Department of Music Teaching in 2015-2016 academic year. For the data collection, "Philosophy Preference Assessment Scale" by Wiles and Bondi (1993), which was adapted to Turkish by Doğanay and Sarı (2003), is used in order to determine music te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 4 publications
1
5
0
17
Order By: Relevance
“…The statistical analyses have revealed that the mean scores of teachers in terms of the educational philosophies are listed in the order as follows: Progressivism, Reconstructionism, Perennialism, and Essentialism. This finding, high mean scores in favor of Progressivism educational philosophy, corroborated to previous research conducted by ; ; Yokuş (2016). On the other hand, in a study by , it was concluded that the participants showed lower level tendencies towards Progressivism and Reconstructionism but moderate level tendencies towards Perennialism and Essentialism.…”
Section: Results Discussion and Suggestionssupporting
confidence: 88%
“…The statistical analyses have revealed that the mean scores of teachers in terms of the educational philosophies are listed in the order as follows: Progressivism, Reconstructionism, Perennialism, and Essentialism. This finding, high mean scores in favor of Progressivism educational philosophy, corroborated to previous research conducted by ; ; Yokuş (2016). On the other hand, in a study by , it was concluded that the participants showed lower level tendencies towards Progressivism and Reconstructionism but moderate level tendencies towards Perennialism and Essentialism.…”
Section: Results Discussion and Suggestionssupporting
confidence: 88%
“…There are many studies in the literature that aim to find out the educational philosophies adopted by teachers or prospective teachers (Altınkurt, Yılmaz & Oğuz, 2012;Çağırgan Gülten & Batdal Karaduman, 2010;Doğanay & Sarı, 2003;Duman, 2008;Duman & Ulubey, 2008;Ekiz, 2007;Koçak, Ulusoy & Önen, 2012;Önen, 2011;Tekin & Üstün, 2008) and that explain educational philosophies with respect to various variables (Altınkurt, Yılmaz & Oğuz, 2012;Aslan, 2014;Aybek & Aslan, 2017;Head, 2015;Beytekin & Kadı, 2015;Biçer, Er & Özel, 2013;Bilgin, 2007;Çalışkan, 2013;Çetin, İlhan & Arslan, 2012;Doğanay, 2011;Doğanay & Sarı, 2003;Ekiz, 2007;Görmez, 2015;Ilgaz, Bülbül & Çuhadar, 2013;Kaya, 2007;Kumral, 2015;Meral, 2014;Özüdoğru, 2010;Yılmaz, Altınkurt & Çokluk, 2011;Yılmaz & Tosun, 2013;Yokuş, 2016). Also, there are studies in the literature that aimed to reveal prospective teachers' perceptions of competence (Aydın & Boz, 2010;Büyükduman, 2006;Diken, 2006;Gencer & Çakıroğlu, 2007;Gercek, Yılmaz, Köseoğlu & Soran, 2006;Küçükyılmaz & Duban, 2006;Savran & Çakıroğlu, 2001;Uygur (2010;…”
Section: Introductionmentioning
confidence: 99%
“…Ancak esasicilik eğitim felsefesini erkek öğretmenlerin daha fazla benimsedikleri görülmüştür. İlgili alan yazın incelendiğinde öğretmen veya öğretmen adaylarının cinsiyetlerinin, sahip oldukları eğitim felsefeleri üzerinde bir etki yaratmadığı sonuçlarına ulaşılmıştır (Aybek & Aslan, 2017;Berkant & Özaslan, 2019;Çelik ve Orçan, 2016;Yokuş, 2016). Buna rağmen Kumral (2015) erkek öğretmen adaylarının, öğretim ortamlarına yönelik daha geleneksel (pozitivist, modernist) düşündüğünü; kadın öğretmen adaylarının ise daha popüler (post pozitivist, yapılandırmacı) düşündüklerini belirtmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified